2021
DOI: 10.1016/j.amsu.2021.102674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine on postoperative bowel movement and defecation after cesarean section

Abstract: Introduction and Importance: Inadequate bowel movement after cesarean section (C-section) can delay the intake of solid diet. Coffee is reported to have beneficial effects on bowel motility after the surgery. This study is designed to evaluate the effects of coffee on bowel movement and defecation following C-section. Methods In this randomized clinical trial study, women undergoing elective C-section at the hospital of (XXX) during 2019–2020 were included. Following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Among the findings of the secondary outcome measures in our study, mean time to first bowel movement (37±6.8 vs. 30±4.8 hours) showed significant differences between the two groups. These findings were in agreement with a study conducted by Zamanabadi et al who found that coffee intake led to shorter postoperative bowel movement in women undergoing C-section 8 . Similar findings were also reported by Parnasa et al and Gkegkes et al Their results concluded that postoperative caffeine consumption led to a significantly shorter time to first bowel movement 18,19 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the findings of the secondary outcome measures in our study, mean time to first bowel movement (37±6.8 vs. 30±4.8 hours) showed significant differences between the two groups. These findings were in agreement with a study conducted by Zamanabadi et al who found that coffee intake led to shorter postoperative bowel movement in women undergoing C-section 8 . Similar findings were also reported by Parnasa et al and Gkegkes et al Their results concluded that postoperative caffeine consumption led to a significantly shorter time to first bowel movement 18,19 .…”
Section: Discussionsupporting
confidence: 93%
“…Several trials have found that coffee administration can reduce postoperative ileus. In a study done by Hasler in 2019 on patients undergoing laparoscopic colorectal elective surgery, coffee was found to decrease the time to nasogastric tube removal and hospital stay 7. Additionally, Zaman Abadi in 2021 in a study on women undergoing C-section found that coffee intake led to shorter postoperative bowel movement and defecation times 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The most common complication reported was the need for reintervention and operation due to vascular injury. 39.5% of patients underwent revision surgery in our study and most of the patients in our surgery received primary repair of the injury 21 .…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, the mechanism of action of coffee on the brain-gut axis with its propulsive effects is not fully understood [16]. While the beneficial effect of coffee consumption on postoperative bowel recovery after gynecologic surgery and cesarean section has been consistently demonstrated in randomized controlled trials (RCTs) [17][18][19], there are still conflicting results regarding coffee and caffeine intake in colorectal surgery, especially with regard to bowel motility [20][21][22][23]. Thus, the primary objective of this meta-analysis was to accurately evaluate the impact of caffeine and coffee consumption on postoperative outcomes after colorectal surgery, with a special focus on bowel recovery, as a potential cost-effective, easily accessible, and practical strategy for POI prevention.…”
Section: Introductionmentioning
confidence: 99%